Banking on Transparency: The Role of Stakeholders Pressure in Indonesian Sustainability Reporting - Renata, Madeline; Widianingsih, Luky Patricia; Cliff Kohardinata (Ilomata International Journal of Tax and Accounting, 2024)
Sustainability reports have become essential for stakeholders in various industries. However, a concerning lack of transparency persists, where reported information may not reflect actual practices. This study examines the influence of three key banking industry stakeholders - employees, government, and customers - on the transparency of sustainability reports. Transparency is measured by the frequency of sustainability reporting (SR) and the level of SR assurance. The study analyzes 38 banking companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. Multiple linear regression is employed as the analytical method. Findings reveal that employee pressure significantly positively impacts the frequency of SR reporting, while public and government pressure shows no such effect. Interestingly, both employee and government pressure positively influence the level of SR assurance, while public pressure again demonstrates no significant impact. This research contributes to a deeper understanding of stakeholder influence on transparency in banking industry sustainability reporting. The findings can assist companies in enhancing their reporting transparency and better meeting stakeholder expectations.